Balancing speed and experience: the cognitive and affective impacts of playback acceleration in digital media consumption - Yueh, Rich; Lim, Jonathan; Li, Ye; Dorri, Rasam (Frontiers in Psychology, 2025)
Playback-speed controls are ubiquitous on media platforms, yet their effects on viewers’ experience and outcomes are not fully understood. We examined how acceleration influences cognitive engagement, affective experience (satisfaction, discomfort, perceived distortions), speaker perceptions, and behavioral intentions, and whether motivational cues (quiz expectancy) shape these effects. Three preregistered experiments exposed adults to either procedural or conceptual videos at standard or accelerated speeds. Studies 2a–2b additionally manipulated quiz expectancy and included a brief objective quiz. Outcomes were assessed with multi-item self-report scales; Study 2a–2b quiz scores provided objective performance. Analyses used ANOVA with study-specific factors. Across studies, faster playback reliably increased perceived distortions and modestly reduced satisfaction. Effects on cognitive engagement, discomfort, and speaker favorability were limited and context-dependent (varying by content type and audience). Quiz expectancy sometimes enhanced engagement at faster speeds, particularly among students. Behavioral intentions to reengage with content showed no reliable differences by speed, and objective quiz performance did not differ by speed. Playback speed is a consequential design variable whose effects depend on content demands, audience characteristics, and motivational context. Thoughtful, context-aware integration of speed controls—especially in educational settings—can help preserve experiential quality without sacrificing efficiency.